The Effect of Type and Duration of Seed Storage on Sugarcane Growth - Parnidi Parnidi; Rully Hamida (Jurnal Penelitian Pendidikan IPA, 2021)
Sugarcane propagation is mostly done by stem cuttings aged 5 to 8 months. Sugarcane seeds in the form of stalks have limited storage capacity, the germination of seeds will decrease rapidly if the seeds are stored for too long time. The high weight and volume for the use of sugarcane seeds is one of the limiting factors if planting is to be carried out far from the seed breeding place. The purpose of this study was to determine the effect of the type and storage time of sugarcane seeds on the growth of sugarcane.The research was conducted at the Karangploso Experimental Garden Balittas in January-December 2016. The research was carried out in the field using a divided plot design with 3 replications. The main plot is the type of seed, namely B1 (bud sett) and B2 (bud chip). As subplots are the storage time P0 (without storage/control), P1 (24 hours storage), P2 (48 hours storage), and P3 (72 hours storage). The results showed that the germination power of bud set did not decrease significantly. The increase in germination and first count germination was noticeable at 24-72 h storage compared to control. The percentage of bud chip seed germination rate decreases with increasing storage time. In the polybags phase, the growth of bud sett seeds is faster than bud chip seeds. The growth of 3 months old plants after transplanting the number of seedlings of bud sets and bud chips was not significantly different. The variables of plant height, stem diameter and number of internodes were significantly different. All the observation variables at the age of 6 months showed no significant difference between bud set seeds and bud chip seeds.